Semántica léxica y cultura lingüística: análisis del vocabulario metalingüístico del español - Loureda Lamas, Óscar (Verbum – Analecta Neolatina, 2004)
There is a wealth of bibliographic material available to the researcher who intends to understand the diVerent models of linguistic analysis. By contrast, far fewer pages have been devoted to the examination of the linguistic ideas implicit in languages, that is to say, to the investigation of the linguistic culture of a community. By means of linguistic cultural expression one can distinguish at least two difeerent realities: on the one hand, the knowledge, attitudes and beliefs about the factors at play in the act of speaking and which in some manner determine it, and, on the other, the notions of language and speaking manifested by distinct languages in their difeerences. My article is concerned with this last element of cultural linguistics. Above all, I am interested in the communal evaluations which help each historical collective to identify their linguistic reality, inasmuch as they reveal a prescientific and intuitive conscience which does not respond to the criteria of any science, though they are not delimitations which seek to study the nature of this reality in detail. This does not mean, however, that they are therefore absurd or unnecessary; in reality they appear daily in the behaviour of the speakers of the language (including that of linguists).